1992
DOI: 10.1111/j.1365-3121.1992.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope geochemistry and structural elements of the Sabina region (Central Apennines, Italy)

Abstract: Various tectonic features are present in the Meso‐Cenozoic basin units of the Sabina region (Central Apennines, Italy): Mio‐Pliocene northeasterly verging thrusts are followed by Plio‐Pleistocene, N‐S oriented right‐lateral strike‐slip faults. Stable isotope geochemistry and examination of meso‐ and microstructures show that strain conditions differed through the course of tectonic history. Carbon and oxygen isotope analyses of the calate‐filled extensional fractures, the sigmoidal veins present between stylol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Meteoric waters infiltrated downward into the tectonic cracks and were channelized through structural conduits within the rock volume, compatible with a scenario of tectonically maintained vertical permeability (e.g., Sibson, 2000;Cox et al, 2001;Rowland and Sibson, 2004). Similar scenarios of fluidassisted tectonic deformation in the central Apennines have been documented in faulted carbonate rocks (e.g., Maiorani et al, 1992;Conti et al, 2001;Ghisetti et al, 2001;Agosta et al, 2008;Smeraglia et al, , 2018, suggesting the interplay between transient permeability at the fault damage zones and mixing of fluids from different reservoirs (meteoric, groundwater, subcrustal). Noteworthy, the AFS provide a case history of fluid-rock interaction in siliciclastic units affecting by extensional faulting.…”
Section: Tectonic Synthesissupporting
confidence: 58%
“…Meteoric waters infiltrated downward into the tectonic cracks and were channelized through structural conduits within the rock volume, compatible with a scenario of tectonically maintained vertical permeability (e.g., Sibson, 2000;Cox et al, 2001;Rowland and Sibson, 2004). Similar scenarios of fluidassisted tectonic deformation in the central Apennines have been documented in faulted carbonate rocks (e.g., Maiorani et al, 1992;Conti et al, 2001;Ghisetti et al, 2001;Agosta et al, 2008;Smeraglia et al, , 2018, suggesting the interplay between transient permeability at the fault damage zones and mixing of fluids from different reservoirs (meteoric, groundwater, subcrustal). Noteworthy, the AFS provide a case history of fluid-rock interaction in siliciclastic units affecting by extensional faulting.…”
Section: Tectonic Synthesissupporting
confidence: 58%
“…The location of earthquake foci defines a NNW-striking fault zone seismically active between about 1.5 and 0.5 km of depth beneath the Lapis Tiburtinus travertine (Gasparini et al, 2002). Previous structural studies (Mattei et al, 1986;Maiorani et al, 1992;Faccenna et al, 1994a,b,c;Sagnotti et al, 1994;Billi et al, 2006b) showed that this fault and the associated brittle deformation are well exposed toward the north in the Jurassic-Miocene marine carbonate strata of the Cornicolani Mountains (Fig. 1).…”
Section: Structural Setting and Hydrologic Frameworkmentioning
confidence: 88%
“…The thermal waters eventually rise along active faults and emerge in the Acque Albule basin (Figs. 1 and 2) with an average temperature of 23°C and pH values between 6.0 and 6.2 (Manfra et al, 1976;Capelli et al, 1987;Pentecost and Tortora, 1989;Maiorani et al, 1992;Pentecost, 1995;Billi et al, 2006b). The complete chemical composition of these waters is provided by Giggenbach et al (1988) and Minissale et al (2002).…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…In the Acque Albule area, tectonics led to the formation of a pull-apart subsiding basin characterized by a north-striking, right-lateral, seismically-active fault system and N40°E-N60°E extensional structures. The fault system is partially overburdened by travertine deposits and crops out in the carbonate Cornicolani Mountains (Maiorani et al 1992;Faccenna et al 1994;Sagnotti et al 1994;Gasparini et al 2002;Florindo et al 2004;Billi et al 2006;Faccenna et al 2008;Petitta et al 2011;Carucci et al 2012).…”
Section: Geologic and Hydrogeologic Settingmentioning
confidence: 99%